INVESTIGATION OF CONTACT FATIGUE AND OPERATING PERFORMANCE OF NI-WC COMPOSITE ELECTROCOATED GEARS - BHAT, KETAN; Avadhani, Maneesh; Gurav, Milind; Patil, Vadiraj; Krishna, M. (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
The objective of the work was to evaluate contact fatigue and operating performance of electrodeposited Ni-WC composite coated gears using experimental technique. The electrodeposited Ni-WC coating was characterized for coating thickness, hardness and crystal structure using Electro-Physik gauge, Rockwell Hardness testing machine and X-Ray Diffraction respectively. The operation condition was estimated using designed test rig and vibration pick with CRO. The results show that coated gears are smoother in operation and offer more resistance to wear and fretting due to increased hardness.